Practical CakePHP Projects - Miller, Cheryl; Omokore, John; Chan, Kai (Apress : Imprint: Apress, 2009)
If you've been using PHP for sometime now and would like to start using a web framework, you'll want to try CakePHP, which is an open source rapid development web framework built on PHP. PHP experts Kai Chan and John Omokore guide you through a variety of practical CakePHP applications. You will work on projects such as a video gallery, unit testing application, an e-commerce app, a blog site, and much more. Practical CakePHP Projects covers the key architectural concepts as well as including mini projects that you can use to enhance your own applications. A friendly introduction for any web programmer looking to choose a PHP framework Real-world projects based on current and future trends Practical CakePHP techniques that you can use right away.